Medical school selection criteria as predictors of medical student empathy: a cross-sectional study of medical students, Ireland - O’Sullivan, Donnchadh M (BMJ Open, 2017)
OBJECTIVES: To determine whether performance in any of the Health Professions Admissions Test (HPAT) sections, most specifically the interpersonal understanding section, correlates with self-reported empathy levels in medical students. SETTING: The study was conducted in University College Cork, Ireland. PARTICIPANTS: 290 students participated in the study. Matching HPAT scores were available for 263 students. All male and female undergraduate students were invited to participate. Postgraduate and international students were excluded. PRIMARY AND SECONDARY OUTCOME MEASURES: Primary measures: HPAT-Ireland and Jefferson Scale of Physician Empathy (JSE) scores were compared including subsection analysis. Secondary measures: comparisons were made between groups such as gender and year of programme. RESULTS: A total of 290 students participated. Males scored significantly higher than females for total HPAT-Ireland (U=7329, z=−2.04, p<0.05), HPAT-Ireland section 1 (U=5382, z=−5.21, p<0.001) and section 3 scores (U=6833, z=−2.85, p<0.01). In contrast, females scored significantly higher than males on HPAT-Ireland section 2 (U=5844, z=−4.46, p<0.001). Females demonstrated significantly higher total JSE scores relative to males (mean score ± SEM: 113.33±1.05vs 109.21±0.95; U=8450, z=−2.83, p<0.01). No significant association was observed between JSE scores and any of the HPAT-Ireland measures (all p>0.05). There was no effect of programme year on JSE scores (all p>0.05). CONCLUSION: The introduction of the HPAT-Ireland test was partly designed to identify students with strong interpersonal skills. A significant finding of this study is that JSE values did not correlate with HPAT-Ireland scores. This study suggests no clear link between scores on a selection test, the HPAT-Ireland, which is designed to assess several skill domains including interpersonal skills, and scores on a psychometric measure of empathy, at any point during medical education.